Iodine Deficiency and Mental Performance: A Review. - Zaleha Md. Isa (Universiti Kebangsaan Malaysia, 2013)
Iodine deficiency disorders (IDD) is responsible for a lot of adverse health effects and it is one of the most common causes of preventable mental impairment. Impaired cognitive function is an outcome of impaire neurodevelopment process during early pregnancy due to iodine deficiency.